FINANCIAL BUSINESS SUPPORT: BANKING SECTOR VS "CORONAVIRUS" CRISIS - Vartsaba , V.; Chubar , O.; Ohorodnyk, V. (The actual problems of regional economy development, 2020)
The negative effects of restrictive measures on prevention of the spread of COVID-19 acute respiratory disease caused by the SARS-CoV-2 coronavirus have led to a significant decline in business activity around the world and have revealed the authorities insolvency to resolve this issue quickly. The purpose of this publication is to study the opportunities of providing financial and credit support to businesses under conditions of counteracting the "coronavirus" crisis that has affected the whole world and has not bypassed Ukraine. The amount of business financial results in 2020 was analyzed in the article. It was found that the losses exceeded the last year's figures more than three times, and the amount of received income was 10% less than the previous year. It was also found that the "coronavirus" crisis significantly affected the Ukrainians economic sentiment, which lowered each component of the indicator of economic sentiment, and the indicator of consumer confidence decrease. Although certain anti-crisis measures are introduced by public authorities, the authors of this study found that declared forms of state incentives for business entities and the amount of financial and credit support are not able to affect the situation stabilization but and can only mitigate and smooth out negative trends. Some trends and features of the Program "Affordable Loans 5-7-9%" was highlighted in the article. It was concluded that nature of the loan structure of this program is investment, as about 80% of loans are used to refinance existing debts. The study practical significance is that the authors propose to intensify the banking sector and to expand preferential lending programs with the participation of the state to overcome the economic consequences of restrictive measures and to stimulate further economic growth.